Реформування міського управління у Волинській губернії (остання третина ХІХ ст.) - Леснича, Пауліна; Lesnycha, Paulina (Східноєвропейський національний університет імені Лесі Українки, 2017)
The peculiarities of the reform the city government in the Volyn province in the last third of the nineteenth century are considered. The regulatory legal acts on the basis of which the transformation of the city authorities was carried out are analyzed. Emphasis is placed on the process of introducing the management in Volyn cities in accordance with the City regulation of 1870 and the City regulation of 1892. The differences in the reforming the city government in cities of state and private property are shown. The problem requires new research regarding of the role of heads of newly formed bodies of the city government in solving important economic problems of the city as well as the reaction of ordinary citizens to the introduction of a new system of urban management. Розглянуто особливості реформування міського управління у Волинській губернії в останній третині ХІХ ст. Проаналізовано нормативно-правові акти, на підставі яких вибирали нові органи міської влади. Увагу акцентовано на особливостях уведення в дію Міського положення 1870 р. та Міського положення 1892 р. на Волині Розкрито відмінності здійснення міської реформи в державних і приватновласницьких містах губернії.
Reforming the City Government in the Volyn Province (the Last Third of the XIX Century)
Keywords: Волинська губернія; місто; міська дума; спрощене громадське управління; Міське положення 1870 р.; Міське положення 1892 р.; Volyn province; city; city council; simplified public administration; City regulation of 1870; City regulation of 1892